Utilization of the AgriTrack Information System to Strengthen Smart Farming Practices in Small-Scale Hydroponic Enterprises - Sholeha, Eka Wahyu; Supriyanto, Arif; Utomo, Hendrik Setyo; Firmansyah, Eka Ridhoni August; Aisyah, Aisyah; Hidayat, Ardhi; Mardhiyatirrahmah, Liny (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
The implementation of smart farming in small-scale hydroponic enterprises is often constrained by high automation costs and technological complexity. This study examines the utilization of the AgriTrack information system as a practical approach to strengthening smart farming practices through structured digital data management. AgriTrack was utilized in a small-scale hydroponic farm using a Software Development Life Cycle (SDLC) Waterfall approach, encompassing system configuration, operational deployment, and evaluation through functional testing and user acceptance testing. The system applies a cycle-based relational data model to manage cultivation records from sowing to harvesting and integrates automated scheduling with Telegram Bot notifications. Testing results indicate a 100% success rate across core operational functions, while user evaluation shows that routine cultivation data recording time was reduced from several minutes to under one minute per entry. Notification delivery was consistently observed within approximately one minute after scheduled triggers, supporting timely operational decisions. These findings demonstrate that AgriTrack effectively strengthens smart farming practices in MSME-scale hydroponic enterprises by improving efficiency and accountability, while providing a scalable foundation for gradual adoption of advanced technologies such as IoT and data analytics.